Avaliação do desenvolvimento biométrico e rendimento de cortes de cabritos das raças Saanen e Alpina - Carlos Augusto Alanis Clemente (2009)
This work aimed evaluates the body development of Saanen and Alpine kids and its productive characteristics. We analyzed fifty one goats, twenty four were Saanen and twenty seven were Alpine. Both breeds has sixty days old and its of body weight (BW) was about 13.4 Kg. These goats received 1.5% from BW of concentrated and hay of coast cross (Cynodon dactylon) to the will, in two daily meals. The animals had been weighed and measured to each 14 days and after 210 days, the animals had been abated. Moreover, the carcass, organs and viscera had been weighed. After 24 hours of cooling, the carcass was divided in commercial cuts. Comparisons between Sannen and Alpine, the Alpine presented higher averages for all biometrics measures, as well as for the BW, empty body weight, hot carcass weight (HCW), cold carcass weight (CCW) and the commercial cuts. Amongst the measures evaluated, the thoracic perimeter (TP) as biometric measure and weight shoulder as commercial cut, presented better correlations with HCW (91.1 and 97%) and CCW ( 91 and 98%), respectively. Moreover, the TP and BL (body length) together, also presented the best equations to predict the BW, with high values of R ² in both the breeds. Therefore, shoulder was the only commercial cut that presented greater meaty tissue ratio from Alpine. The weight of the non-carcass components was higher in Alpine breed and this difference was found as for the viscera weight as for no edible components. In conclusion, the Alpine breed had greater weight in the commercial cuts and a higher income meaty tissue in the shoulder. In both breeds, the TP and BL together was the best measure for prediction of the body weight.